Xanthones from Garcinia Malaccencis improve Glut4 aswell as decreased Pparγ activation on adipocytes - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Darnis, Deny Susanti; Ichwan, Solachuddin J. A. (2013)
In this study, we used α-mangostin, the major xanthone compounds and β-mangostin from Garcinia malaccensis Hk.f (locally known as “manggis burung”) and evaluate its in vitro activities on adipocyte differentiation, glucose uptake and related gene expression (pparγ and glut4) mechanism. Firstly, we elucidated the inhibitory effect of the compounds on lipid accumulation of 3T3-L1 preadipocytes by using Oil red O staining. Cell treated with α-mangostin and β-mangostin dose-dependently was found to inhibit the cytoplasmic lipid accumulation as well as adipogenic differentiation of preadipocyte. All compounds showed high lipid inhibition activity at 50 μg/mL concentration (P < 0.05) compared to MDI treated cells. Besides, glucose uptake activity was investigated in differentiated adipocytes using a radioactive-labelled glucose by Liquid Scintillation Counter. The insulin-induced 2-deoxy-D-[3H] glucose uptake activities were significantly improved with increasing the concentration of the test compounds. Further evaluation with the quantitative real time polymerase chain reaction (qRT-PCR) shows that α-mangostin and β-mangostin reduced the expression of pparγ genes during adipocyte differentiation. At the same time, induction of glucose uptake by α-mangostin and β-mangostin was accompanied by the increased mRNA expression of glut4 genes. Since downregulation of pparγ has been reported to be activated during inhibition of adipogenesis and enhance expression of glut4 has been shown to be increased during glucose uptake we demonstrated that both compounds follow the antiobesity pathways. Taken together, these results indicate that xanthones derived from Garcinia malaccencis may be a candidate for preventing metabolic disorders such as obesity.